Quality of life of cardiac patients eligible for implantation of cardiac pacemakers - Antônio, Izelina Helena de Freitas; Barroso, Thatiara Lima; Cavalcante, Agueda Maria Ruiz Zimmer; Lima, Luciano Ramos de (Revista de Enfermagem UFPE on line, 2010)
ABSTRACT Objective: to determine the quality of life (QL) of cardiac patients eligible for implantation of a pacemaker (PM) in a cardiac hospital in the inland cities of Goiás States. Method: a cohort study, prospective, longitudinal quantitative approach. Purposeful sample applied to 25 patients who underwent implantation in the first half of 2009. The instrument used was the Short Form Healthy Survey (SF-36). The data were analyzed using Statistical Package for Social Sciences (SPSS) 15.0. The study was approved by the Ethics in Research of the University Center of Annapolis, protocol number 183/2008. Results: Chagas was the most frequent indication for implantation (68%), time of diagnosis of 1 to 25 years (56%), and 13 patients were undergoing treatment and 64% of patients with 1 insertion of pacemaker (PM), without changing so far. The major areas of life scores were Social Aspects (M=72,7), and the minor ones were Functional Capacity (M=31,6), demonstrating that QL is compromised because most of the areas did not exceed the average 50. There was no significance between age and QOL (p>0,05). Conclusion: we conclude that cardiac patients have significant negative impact on QL. Descriptors: quality of life; pacemaker, artificial; nursing; heart diseases; cardiac pacing, artificial; nursing assessment; chagas disease. RESUMO Objetivo: determinar a qualidade de vida (QV) dos cardiopatas elegíveis à implantação de marca-passo (MP) em um hospital no interior de Goiás. Método: estudo de coorte, prospectivo, longitudinal, quantitativo. Amostra intencional aplicada a 25 pacientes submetidos ao implante de MP no primeiro semestre de 2009. O instrumento utilizado foi o Short Form Healthy Survey (SF-36). Os dados foram analisados pelo Statistical Package for the Social Sciences (SPSS) 15.0. O estudo foi aprovado pelo Comitê de Ética em Pesquisa do Centro Universitário de Anápolis, com protocolo 183/2008. Resultados: Chagas foi a indicação mais frequente para implante (68%), com tempo de diagnóstico de 1 a 25 anos (56%), sendo que 13 pacientes realizavam tratamento e 64% dos pacientes com a 1ª inserção de MP. O domínio de maior escore para QV foi os Aspectos Sociais (M=72,7) e menor Capacidade Funcional (M=31,6), demonstrando que a QV é comprometida já que a maioria dos domínios não ultrapassou a média 50. Não houve significância entre idade e QV (p>0,05). Conclusão: os cardiopatas apresentam importante impacto negativo na QV. Descritores: qualidade de vida; marca-passo artificial ; enfermagem; cardiopatias; estimulação cardíaca artificial; avaliação em enfermagem; doença de chagas. RESUMEN Objetivo: determinar la calidad de vida (CV) de los pacientes cardiacos elegibles para la implantación de un marcapasos (PM) en un hospital cardíaco del interior de Goiás. Método: estudio de cohorte, prospectivo, longitudinal de enfoque cuantitativo. Con propósito de la muestra aplicada a 25 pacientes que se sometieron a la implantación en el primer semestre de 2009. El instrumento utilizado fue la Encuesta Healthy Short Form (SF-36). Los datos fueron analizados mediante el Statistical Package for Social Sciences (SPSS) 15,0. El estudio fue aprobado por la Ética en la Investigación del Centro Universitario de Anápolis, con el protocolo 183/2008. Resultados: Chagas fue la indicación más frecuente para implante (68%), el tiempo de diagnóstico de 1 a 25 años (56%), y 13 pacientes fueron sometidos a tratamiento y el 64% de los pacientes con la inserción de 1 MP, ningún cambio en la tiempo. La principale área de cuentas de la vida fue los aspectos sociales (M=72,7), y los menores fueron la capacidad funcional (M = 31,6). No hubo significación entre la edad y la calidad de vida (CV) (p>0,05). Conclusión: se concluye que los pacientes cardíacos tienen un impacto negativo significativo en la CV. Descriptores: calidad de vida; marcapaso artificial; enfermería; cardiopatías; estimulación cardíaca artificial; evaluación en enfermería; enfermedad de chagas.